A biography of Archbishop Richard Neile (1562-1640) - Foster, A (1978)
This thesis provides a biography of a man whose importance in Church and State in the first half of the seventeenth century has never been fully appreciated. It is divided into eight sections, the first of which considers Neile's humble origins, education at Westminster and Cambridge, and patronage at the hands of the Cecil family and Archbishop Bancroft. It was as Dean of Westminster that Neile's exceptional talents as an administrator first became generally apparent. It was also at this time that he won the affection of King James I - the decisive factor in Neile's elevation to the episcopate and rapid advancement through the dioceses of Rochester, Lichfield and Coventry, Lincoln and Durham. Attention is focused on Neile's role as a bishop and on factors behind his administrative success, such as his ability to select and train able subordinates - clergymen and civil lawyers alike. Other chapters highlight more unusual facets of his career, such as his role as Lord Lieutenant of Durham County Palatine. Even his work in the House of Lords reveals wider interests than those normally expected of a bishop. Discussion of Neile's religious beliefs contributes to our knowledge of English Arminianism. Neile emerges as the great patron of this party and the practical effects of his views can be seen in his work as a Privy Councillor and as a judge in the courts of Star Chamber and High Commission. The implementation of Arminian policies at Winchester and after his final appointment as Archbishop of York was one of the major causes of the English Civil War.